Health care workers safety: screening and immunization: a review - Al Johani, Abdulrahman A.; Karuppiah, Karmegam; Al Nozha, Omar M.; Alya O., Al Mutairi; K. C. Mani, Kulanthayan; Sambasivam, Sivasankar (The Malaysian Public Health Physicians Association, 2017)
The paper puts forth the need for health care workers safety whilst undertaking their job on a daily basis. Presently there are number of factors that are directly linked to the safety of health care workers. However, Occupational Health is very important and useful for health workers that are exposed to their job hazards. Every year, many lives are lost because of the spread of infections in hospitals. Every hospital’s occupational health departments should ensure that all new staff are vaccinated to protect them against microorganisms carried by other patients, and with vaccinated against preventable diseases. This will help to prevent the health workers from occupational exposure to patients’ blood or any other bodily substances, including injury from sharp objects, and also guarantees that the new employees does not infect the patients with infectious diseases. Furthermore, all the new staff should be screened for blood borne pathogenic diseases.